Related Risk Factors and Treatment Management of Psoriatic Arthritis Complicated With Cardiovascular Disease - Zheng, Zhoulan; Guo, Qianyu; Ma, Dan; Wang, Xuexue; Zhang, Chengqiang; Wang, Haiyao; Zhang, Liyun; Zhang, Gailian (Frontiers in Cardiovascular Medicine, 2022)
Psoriatic arthritis (PsA) is a chronic autoimmune inflammatory joint disease related to psoriasis (PsO). The risk of PsA patients with cardiovascular disease (CVD) is significantly higher than that of the general population. At present, the relevant mechanism is not clear, chronic inflammation and traditional cardiovascular risk factors are the most important factors for the increased risk of CVD in PsA patients. Early assessment of the risk of PsA patients with CVD, and active control of the disease activity of PsA patients and intervention of traditional cardiovascular risk factors can delay the progression of CVD risk. This article reviews the epidemiology and pathogenesis between PsA and CVD, and reviews the latest developments in the risk assessment and management of CVD in PsA patients.